Government Effectiveness and Good Governance Index: The Case of Indonesia - Ihyani Malik (Journal of Governance, 2024)
Good governance is a critical aspect of organizational culture, especially in the public sector. This article explores the relationship between government effectiveness and good governance, focusing specifically on the Indonesian context. Understanding this relationship is crucial for organizational culture studies, as it highlights the impact of leadership, policy-making, and administrative competence on the overall functioning of an organization. The primary aim is to assess how the effectiveness of government institutions in Indonesia impacts the broader dimensions of good governance. The author obtained data through the UN, World Bank, WJP, and CGGI websites, and visualized them for easy understanding.  The findings indicate a significant correlation between government effectiveness and the quality of governance. Improved bureaucratic efficiency, policy implementation, and service delivery are closely linked with higher scores on the governance index. However, challenges in combating corruption and ensuring consistent rule of law remain notable hurdles. The study concludes that enhancing government effectiveness is crucial for the advancement of good governance in Indonesia. While progress has been made, sustained efforts are required to address ongoing challenges. The findings of the study provide lessons on how organizational culture in government institutions can be improved or reformed.